Pediatric nutrition - Kleinman, Ronald E.; Greer, Frank R. (American Academy of Pediatrics, 2020)
The new eighth edition of this bestselling AAP policy manual on pediatric nutrition has been significantly updated and includes many new contributing authors. This valuable reference covers how nutrients influence and direct growth and development, as well as immediate and long-term health, from birth through adolescence. This evidence-based manual reflects the current policies and practices recommended by the American Academy of Pediatrics Committee on Nutrition. New in the eighth edition:New chapter on Pediatric Global NutritionOther chapters have been completely reorganized, based on new information from publications in nutritional science and new evidence based guidelines recommending changes in practice. New policy statement on sugary drinks, and new clinical reports on food insecurity, fruit juice consumption, non-nutritive sweeteners, fish and shellfish consumption, and use of donor human milk for the preterm infantUpdated growth charts for preterm infants after birth including BMI.